Alcohol and tobacco use among maltreated and non‐maltreated adolescents in a birth cohort. (16th January 2014) - Mills, Ryan; Alati, Rosa; Strathearn, Lane; Najman, Jake M.
Abstract Aims This study examines whether child maltreatment experience predicts adolescent tobacco and alcohol use. Methods The subjects were participants in the Mater‐University Study of Pregnancy (MUSP), a birth cohort of 7223, of whom 5158 (71.4%) were available for analysis at the 14‐year follow‐up. Child protection history was obtained from the state's child protection agency and confidentially linked. Exposure to reported child maltreatment was the primary predictor variable. The outcome variables were self‐reported smoking and alcohol use. Associations were adjusted for potential confounders. Results Reported child maltreatment was associated with early adolescent smoking [odds ratio (OR) 1.76, 95% confidence interval (CI) = 1.32–2.34] after adjustment for socio‐demographic variables and coexisting alcohol use. Both neglect/emotional abuse (OR 2.03, 95% CI = 1.20–3.42) and neglect/emotional abuse that included physical abuse (OR 1.85, 95% CI = 1.19–2.88) were associated with smoking after full adjustment, including for coexisting alcohol use. After full adjustment, including coexisting smoking, only child neglect/emotional abuse predicted early adolescent alcohol use (OR 1.78, 95% CI = 1.06–2.97), but not the other types of maltreatment. Conclusions Reported child maltreatment predicts early adolescent smoking after adjusting for alcohol use, but does not predict alcohol use after adjustment for smoking. Both smoking and alcohol use are predicted by reported child neglect. Early adolescent smoking is also predicted by multi‐type maltreatment that includes physical abuse.